Blogs as a Tool for Sharing Organizational Knowledge: A Case Study of Medical Clinic Center, UUM - Masoud, Khalifa Salem Saed (2009)
Application of information technology in our ways of doing things has become inevitable. Such innovations are now being introduced in an ideal working environment to create a knowledge workforce where vital knowledge relating to the activities of a working environment including expertise is shared among workers. Such approach facilitates a proper workflow and tells on the job's efficiency. In this study, we are to consider Blogs as a tool for sharing organization knowledge choosing UUM medical clinic center as the case study. Qualitatively, the study will determine the usage of Blogs for sharing organizational knowledge at UUM medical clinic center. Also Blogs prototype will be developed for the case study and usability testing will equally be conducted.